(untitled) (Journal of Scientific Research, 2009)
The conventional method for designing a fixed bed adsorption unit has been discussed. The method is based on the data obtained from an adsorption column test. The characterization of an adsorption system, however, is performed in a laboratory batch experiment. It is shown that the conventional method does not make proper use of the physico-chemical parameters of an adsorption system determined by batch test. Also the method fails to predict the performance of an adsorption unit, if the operating condition differs from that under which the column test has been conducted for design purposes. New design equation has been proposed for both ‘Constantly Stirred Tank Reactor (CSTR)’ and ‘Plug Flow Reactor (PFR)’ type adsorption units. The equation predicts the performance of a reactor type adsorption unit under varying operating conditions. The proposed method is based only on the data obtained in batch experiment. Keywords: Adsorption; Unit design; Reactor; Optimal Operation, Dosage; Coefficient of utilization. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i3.2592 J. Sci. Res. 1 (3), 450-460 (2009)